Artificial polydopamine interface for high‐performance ambient particulate matter removal at large velocity. Issue 2 (9th March 2023) - Tian, Enze; Liu, Jun; Gao, Yilun; Mo, Jinhan; Zhang, Shaolin; Bai, Xuedong; Liu, Kehai; Xu, Guiyin; Liu, Kaihui
Abstract: Ambient particulate matter (PM) has been identified as the fourth‐ranking risk factor for mortality globally, and efficient ventilation filtration technologies are urgently needed. In most previous trials, however, high filtration efficiency was achieved either at a low face air velocity or at a large pressure drop cost. Here, nine coarse filters with in situ polydopamine (PDA) coatings were reported, which significantly improved the efficiency‐pressure drop‐energy consumption performance. By optimizing the filter substrate and synergistically modulating the electric fields, the artificial PDA coarse filter showed a high filtration efficiency of 96.9% for 0.3–0.5 μm particles, and a low pressure drop of 9.2 Pa at 1 m/s air velocity. At an extremely large air velocity of 4 m/s, the filtration efficiency remained as high as 94.3% for 1–3 μm particles. This work offers the engineering application opportunity for high‐air‐velocity filtration, paving the way to a safe, healthy, and energy‐saving environment. Abstract : Self‐assembled PDA increased the filtration efficiency and reduce the pressure drop (up to 54%) of the coarse substrate filters.